2014
DOI: 10.14697/jkase.2014.34.5.0511
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Investigation of the Imaginative Writing Processes of Middle School Students

Abstract: In this study, we conducted an exploratory investigation of the imaginative writing processes of middle school students. Twelve 8th graders were asked to imagine and write about the daily life of atoms, assuming that they became specific atoms for themselves. The think-aloud method was used to investigate students' writing processes. We recorded students' writing processes, and also collected the data through interviews to clarify ambiguities in their writing processes. The analyses of the results revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…In the exploratory research conducted by Yang, et al, (2014), it revealed that the imaginative writing process of science students in understanding a particular science content follows a process from retrieving information, generating ideas, and integrating the retrieved information with the ideas on writing. Moreover, Gillen, et al, (2020) explained that to write effectively and creatively about science requires a deeper understanding of the underlying scientific concepts than traditional examinations.…”
Section: Introductionmentioning
confidence: 99%
“…In the exploratory research conducted by Yang, et al, (2014), it revealed that the imaginative writing process of science students in understanding a particular science content follows a process from retrieving information, generating ideas, and integrating the retrieved information with the ideas on writing. Moreover, Gillen, et al, (2020) explained that to write effectively and creatively about science requires a deeper understanding of the underlying scientific concepts than traditional examinations.…”
Section: Introductionmentioning
confidence: 99%
“…하였다 (Park & Choi, 2014). 마찬가지로 Nam et al(2011) (Nam, Lee & Lee, 2004 (Shin et al, 2013), 학생들의 과학에 대한 흥미에도 영향을 미쳤다 (Yang, Lee & Noh, 2014;Hand et al, 2004;Owens, 2000). (Kang, Jo & Noh, 2013 (You et al, 2013 (Hayes & Flower, 1980 (Flower & Hayes, 1981 (Dewey, 1933;Schon, 1983 (Park, Choi, & Lee, 2008…”
unclassified